KRITERIA HOMESTAY DI DESA WISATA YANG MEMENUHI PRINSIP-PRINSIP WISATA HALAL : SEBUAH KAJIAN TEORI - Lalu Adi Permadi; Muttaqillah Muttaqillah; Weni Retnowati (Master of Management, Mataram University, 2021)
This theoretical review aimed to discuss about homestay criteria that has been accepting halal tourism principles that can be implemented in the rural tourism. This because the need of adjustment in the pandemic era and the industry must adopt the current condition. The criteria will be useful for the researcher and the assesors for the feasibility of homestay as a halal homestay in this pandemic era and after.Keywords:Homestay, halal, tourism, rural, principles